Correlation analysis between lightning flashes and rainfall rate during a flash flood thunderstorm - Norbayah Yusop; Mohd Riduan Ahmad; Tan Shea Ching; Shamsul Ammar Shamsul Baharin; Mona Riza Mohd Esa; Muhammad Abu Bakar Sidik (Institute of Advanced Engineering and Science, 2022)
This paper presents the correlation analysis between lightning flashes and the rainfall rate of a thunderstorm when a flash flood event happened in Melaka on 11 August 2020. Four types of data have been collected from the electric field mill (EFM), fast antenna (FA) system, constant altitude plan position indicator (CAPPI) radar and world wide lightning location network (WWLLN). Two storms have been detected by the EFM occurred between 04:00:00 and 14:00:00. The FA system recorded a total of 33 lightning flashes had detected with the highest number occurrence of flashes which positive narrow bipolar event (+NBE) around 21 flashes, the maximum rainfall rate and reflectivity have been detected by radar during the first storm were 8 mm h-1 and 37 dBZ, respectively (light rain). During the second storm, there was a total of 980 lightning flashes detected by the FA system with the highest number occurrence of flashes around 429 flashes (IC), the highest value of rainfall rate and reflectivity is 50 mm h-1 and 50 dBZ, respectively (heavy rain). Analyses of the lightning and rainfall rate data also show a close link between the occurrence of major thunderstorms systems and flash flooding on a regional scale.